Empirical Correlations for Viscosity of Polyacrylamide Solutions with the Effects of Temperature and Shear Rate. II - Hashmet, M.R. (Taylor and Francis Inc., 2014)
Apparent viscosity measurements have been made to characterize the effects of shear rate and temperature on the partially hydrolyzed polyacrylamide solutions. The power-law model for the viscosity behavior has been modified to develop empirical correlations that combine effects of shear rate and temperature. Nonlinear regression was performed on the experimental data to develop the proposed correlation. The viscosities of the polymer solutions were measured in the temperature range of 25°C to 80°C, while the shear rate was varied from 1 to 1000 1/s. The proposed correlation should prove supportive for the preliminary selection of the polymers for enhanced oil recovery applications. © 2014 Taylor & Francis Group, LLC.